Antiestrogens: structure-activity relationships and use in breast cancer treatment. (January 2017) - Traboulsi, T; El Ezzy, M; Gleason, J L; Mader, S
Abstract : About 70% of breast tumors express estrogen receptor alpha (ERα), which mediates the proliferative effects of estrogens on breast epithelial cells, and are candidates for treatment with antiestrogens, steroidal or non-steroidal molecules designed to compete with estrogens and antagonize ERs. The variable patterns of activity of antiestrogens (AEs) in estrogen target tissues and the lack of systematic cross-resistance between different types of molecules have provided evidence for different mechanisms of action. AEs are typically classified as selective estrogen receptor modulators (SERMs), which display tissue-specific partial agonist activity (e.g. tamoxifen and raloxifene), or as pure AEs (e.g. fulvestrant), which enhance ERα post-translational modification by ubiquitin-like molecules and accelerate its proteasomal degradation. Characterization of second- and third-generation AEs, however, suggests the induction of diverse ERα structural conformations, resulting in variable degrees of receptor downregulation and different patterns of systemic properties in animal models and in the clinic.